Clinical results of and patient satisfaction with cervical laminoplasty for considerable cord compression with only slight myelopathy - Neo, Masashi (Springer-Verlag, 2011)
PURPOSE: There is no established consensus on the indications for surgery in patients with considerable cord compression but only slight myelopathy. The purpose of this study is to stimulate discussion about the indications for surgery in these patients. METHODS: The records of consecutive patients who underwent cervical laminoplasty (CLP) during 3.5 years were reviewed. Those patients whose pre-operative Japanese Orthopaedic Association score (JOA score, maximum 17) for cervical myelopathy was 16 points or more, indicating that they had very slight myelopathy, were selected. The postoperative JOA scores of these patients were checked via a chart review, and they were sent a survey asking about their degree of satisfaction with the results of surgery. RESULTS: Of 143 patients who underwent CLP, 14 presented with a preoperative JOA score of 16 or more. No patients showed a postoperative deterioration in JOA score. Nine patients complained of pre-operative hand numbness and this symptom disappeared postoperatively in seven cases. Most patients were satisfied with the results of the surgery: “very satisfied” in 11 cases and none selected “slightly dissatisfied” or “very dissatisfied”. CONCLUSIONS: We believe that surgery can rescue well-informed and deliberately selected patients with only slight myelopathy, because their symptoms improve and they are freed from persistent anxiety.